A study on the impact of DRG payment on physicians’ prescribing behavior in China: a case study of a healthcare consortium in J City - Wang, Zhenguo; Li, Li; Cui, Yuwen (Frontiers in Public Health, 2025)
As one of the effective strategies adopted by countries worldwide to mitigate the rapid growth of healthcare expenditures, the DRG (Diagnosis-Related Group) payment system has been implemented in developed Western countries for both outpatient and inpatient care, focusing on costs associated with medical technologies, ancillary services, nursing care, and other healthcare-related expenses. However, in China, the excessive rise in consumable medical costs, particularly for pharmaceuticals, remains a primary driver of unreasonable healthcare expenditure growth. This study takes a healthcare alliance in City J, China, encompassing primary, secondary, and tertiary public hospitals, as a case example. By combining qualitative interviews with quantitative research methods, it explores the impact of DRG payment on physician prescribing behaviors. The results indicate that the DRG payment system significantly influences physician prescribing practices, a finding that holds after a series of robustness checks. Moreover, the effect varies across hospitals of different levels, with the DRG payment system having a more pronounced impact on pharmaceutical costs for acute ischemic stroke cases with two or fewer comorbidities. Therefore, the DRG payment system holds significant implications for the rational allocation of healthcare resources in China.